Total grain-size distribution of four subplinian-Plinian tephras from Hekla volcano, Iceland: implications for sedimentation dynamics and eruption source parameters - Janebo, MH; Houghton, BF; Thordarson, T; Bonadonna, C; Rebecca Carey (2018)
The size distribution of the population of particles injected into the atmosphere during a volcanic explosive eruption, i.e., the total grain-size distribution (TGSD), can provide important insights into fragmentation efficiency and is a fundamental source parameter for models of tephra dispersal and sedimentation. Recent volcanic crisis (e.g. Eyjafjallajökull 2010, Iceland and Córdon Caulle 2011, Chile) and the ensuing economic losses, highlighted the need for a better constraint of eruption source parameters to be used in real-time forecasting of ash dispersal (e.g., mass eruption rate, plume height, particle features), with a special focus on the scarcity of published TGSD in the scientific literature. Here we present TGSD data associated with Hekla volcano, which has been very active in the last few thousands of years and is located on critical aviation routes. In particular, we have reconstructed the TGSD of the initial subplinian–Plinian phases of four historical eruptions, covering a range of magma composition (andesite to rhyolite), eruption intensity (VEI 4 to 5), and erupted volume (0.2 to 1 km 3 ). All four eruptions have bimodal TGSDs with mass fraction of fine ash (<63 μm; m 63 ) from 0.11 to 0.25. The two Plinian dacitic-rhyolitic Hekla deposits have higher abundances of fine ash, and hence larger m 63 values, than their andesitic subplinian equivalents, probably a function of more intense and efficient primary fragmentation. Due to differences in plume height, this contrast is not seen in samples from individual sites, especially in the near field, where lapilli have a wider spatial coverage in the Plinian deposits. The distribution of pyroclast sizes in Plinian versus subplinian falls reflects competing influences of more efficient fragmentation (e.g., producing larger amounts of fine ash) versus more efficient particle transport related to higher and more vigorous plumes, displacing relatively coarse lapilli farther down the dispersal axis.